TATHWIR KITAB AL-AJURUMIYAH WA FA'ALIYATUHA FI TADRIS AL-QAWA'ID BI MADRASAH TSUNAIYAH AL-LUGHAH AL-TSANAWIYAH AL-ISLAMIYAH - A Samsul Ma'arif (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2017)
The students of Islamic senior High school of Bilingual Batu learn Nahwu from Ajurumiyah by using some methods. Those are memorizing and understanding the rules and its examples in the class. However, some of students still do some errors in writing and speaking Arabic sentences. Moreover, the book that they use is not efficient because there is no exercise that can help them to understand the rules and practice the rules in reading, writing and speaking. The researcher conducted this research by using RD (Research Development) method and follows the model of Dick Carey in developing the Nahwu’s textbook adapted from Ajurumiyyah.